Knowledge management and organizational performance: a qualitative study of selected institutions of higher education in Malaysia - Leong, Jin Cheong (2018)
The Ministry of Education in Malaysia is striving towards achieving excellent performance and becoming centre of education excellence in Asia. KM practices within institutions of higher education are important to sustaining competitiveness and contribute towards the nation. The aim of this research was to understand more about KM practices within institutions of higher education, the strengths and weaknesses associated with KM practices, and ways to improve KM practices which lead to greater organizational performance. The conceptual framework covered 3 broad categories which were organizational architecture, organizational culture, and human resource development which included tacit and explicit knowledge and supported by organizational learning framework to facilitate KM practices. Semi structured interviews were conducted among 5 institutions to gather responses from 11 respondents. The findings shown that culture was the most important aspect to facilitate KM effectively which lead to excellent organizational performance. The results also confirm that KM practices could be enhanced where there is friendly knowledge sharing culture with improved organizational architecture and effective human resource development policies.